Neuro-cognitive performance is enhanced during short periods of microgravity - Wollseiffen, P.; Vogt, T.; Abeln, V.; Strüder, H. K.; Askew, C. D.; Schneider, S. (Physiology & Behavior, 2016)
There is increasing interest in the effects of microgravity on cognitive processing, particularly as it relates to the potential for human space travel. While findings to date are quite inconsistent, studies reporting a decrement in cognitive performance have generally not been able to distinguish between the direct influence of microgravity, and any associated influence of stress. Furthermore, the currently available findings are primarily based on behavioral observations, and there is a need to better understand the underlying neurophysiological responses.